REVICTIMIZATION IN CASES OF MOTOR VEHICLE THEFT - Taufik, Zahratul Ain; Nirmala, Atika Zahra; Rahmania, Nunung (fakultas hukum universitas PGRI Semarang, 2024)
A crime committed against a person who then experiences the same crime on the same object is called revictimization or double victimization. Revictimization or double victimization occurred in the Mataram City area, NTB around 2016 and 2018 where the victim with the initials YIM experienced the loss of a motor vehicle twice and repeated on the same motorcycle, the first theft in 2016 and the second theft in 2018. The incident is not an ordinary event that should be ignored. The incident is then deemed necessary to be studied more deeply and related to how a person's role in living his daily life so that the person can become a victim of crime repeatedly on the same crime object.This research is a type of empirical legal research using a descriptive qualitative approach with a case approach carried out by first reading and analyzing literature on legislation related to the legal issues under study. This research serves to see the extent of the victim's role in revictimization of motor vehicle theft, in writing it is necessary to know how the victim's role in living his daily life so that he can become a victim of crime repeatedly on the same crime object. The results of this study conclude that victims of crime as Participating victims, namely someone who unconsciously commits negligent acts or acts that easily make themselves a victim.